2015
DOI: 10.5901/mjss.2015.v6n6p519
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis of Business Learners’ Needs

Abstract: With the increasing aim of matching the objectives of the language course to learners' requirements, the process of Needs Analysis and Identification (NAI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…These results contrast with other studies on ESP, where the main interest seems to be found in oral skills (Benabdallah, 2014) and vocabulary (Mitra, 2014). As stated above, the number of reading activities is prominent in both textbooks, whereas it is one of the last aspects to be considered in the needs analyses carried out by Benabdallah (2014) and Mitra (2014). Furthermore, even though there is no specific mention of language for specific purposes in the CEFR, the last version of this document (2018) states the importance of mediation in the development of communicative competence.…”
Section: Skills and Type Of Instructioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results contrast with other studies on ESP, where the main interest seems to be found in oral skills (Benabdallah, 2014) and vocabulary (Mitra, 2014). As stated above, the number of reading activities is prominent in both textbooks, whereas it is one of the last aspects to be considered in the needs analyses carried out by Benabdallah (2014) and Mitra (2014). Furthermore, even though there is no specific mention of language for specific purposes in the CEFR, the last version of this document (2018) states the importance of mediation in the development of communicative competence.…”
Section: Skills and Type Of Instructioncontrasting
confidence: 99%
“…In terms of language functions, students report on the need for learning to give instructions, request information from patients, and offer help and treatments. In the realm of Business English, Benabdallah (2014) concludes that students are particularly interested in learning specific vocabulary and developing language skills in this order of importance: speaking, listening, writing and reading.…”
Section: Esp Materials Evaluationmentioning
confidence: 99%